Inhibition of New Delhi Metallo-β-Lactamase 1 (NDM-1) Producing Escherichia coli IR-6 by Selected Plant Extracts and Their Synergistic Actions with Antibiotics - Chandar, Brinda; Poovitha, Sundar; Ilango, Kaliappan; MohanKumar, Ramasamy; Parani, Madasamy (Frontiers in Microbiology, 2017)
Improper use of antibiotics has led to a great concern in the development of pathogenic microbial resistance. New Delhi metallo-β-lactamase 1 (NDM-1) producing bacteria are resistant to most of the β-lactam antibiotics, and so far, no new compounds have been clinically tested against these bacteria. In this study, ethanol extracts from the leaves of 240 medicinal plant species were screened for antibacterial activity against an NDM-1 E. coli strain. The extracts that showed antibacterial activity were then tested for minimum inhibitory concentrations (MICs) and zones of inhibition. The extract from Combretum albidum G. Don, Hibiscus acetosella Welw. ex Hiern, Hibiscus cannabinus L., Hibiscus furcatus Willd., Punica granatum L., and Tamarindus indica L. showed bactericidal activity between 5 and 15 mg/ml and the MIC was between 2.56 and 5.12 mg/ml. All six plant extracts inhibited activity of the NDM-1 enzyme in vitro, and the IC50 value ranged between 0.50 and 1.2 ng/μl. Disruption of bacterial cell wall integrity by the plant extracts was clearly visible with scanning electron microscopy. Increases in membrane permeability caused 79.4% to 89.7% bacterial cell deaths as investigated by fluorescence-activated cell sorting. All the plant extracts showed synergistic effects when combined with colistin (ƩFIC = 0.125 to 0.375), meropenem (ƩFIC = 0.09 to 0.313), and tetracycline (ƩFIC = 0.125 to 0.313). Thus, the plant extracts can be fractionated for the identification of active compounds, which could be used as new antibacterial compounds for the development of drugs against NDM-1 E. coli in addition to their use in combination therapy.